The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11103-015-0390-2
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the complex molecular evolution and expression of polygalacturonase gene family in Brassica rapa ssp. chinensis

Abstract: Polygalacturonases (PGs) participate in pectin disassembly of cell wall and belong to one of the largest hydrolase families in plants. In this study, we identified 99 PG genes in Brassica rapa. Comprehensive analysis of phylogeny, gene structures, physico-chemical properties and coding sequence evolution demonstrated that plant PGs should be classified into seven divergent clades and each clade's members had specific sequence and structure characteristics, and/or were under specific selection pressures. Genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 66 publications
5
30
0
2
Order By: Relevance
“…In accordance with previous research, we found that more than half SlPGs of Group I belonged to Clade E and were also defined as being expressed ubiquitously (Figure 4, Table S3) which further proved the previous theory that the Clade E members of PG family are possibly ancient proteins and are fundamental and indispensable in almost all plant organs of different species [7,10]. The PG genes of Clades C, D, and F may be associated with flower development, and the main expression pattern of PGs in clades C and F may be different between the grasses and dicots [7,9,10,12]. Coincidentally, most PGs of Clades C and D can also be observed to show flower-specific expressions in tomato.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…In accordance with previous research, we found that more than half SlPGs of Group I belonged to Clade E and were also defined as being expressed ubiquitously (Figure 4, Table S3) which further proved the previous theory that the Clade E members of PG family are possibly ancient proteins and are fundamental and indispensable in almost all plant organs of different species [7,10]. The PG genes of Clades C, D, and F may be associated with flower development, and the main expression pattern of PGs in clades C and F may be different between the grasses and dicots [7,9,10,12]. Coincidentally, most PGs of Clades C and D can also be observed to show flower-specific expressions in tomato.…”
Section: Discussionsupporting
confidence: 71%
“…Phylogenetic analysis of the PG gene family has been carried out in many studies, from the initial classification of three Clades (A, B, and C) to the adjustment and expansion of the six and seven Clades (A to F and A to G) [2,5,10,12]. In this study, the tomato PG gene family was classified by the A to G classification according to the analysis of their phylogenetic tree as in the previous research about the PG gene family of C. sativus and B. rapa [8,12]. The analysis of the structure of introns and exons and the conserved motif and domain of tomato PG genes revealed that Clades A, B, and F contained relatively more introns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations